2021
DOI: 10.21203/rs.3.rs-744803/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seeds of phase transition to thermoacoustic instability

Abstract: Tackling the problem of emissions is at the forefront of scientific research today. While industrial engines designed to operate in stable regimes produce emissions, attempts to operate them at "greener" conditions often fail due to thermoacoustic instability. During thermoacoustic instability, hazardous high amplitude periodic oscillations lead to failure of these engines in power plants, aircrafts and rockets. Yet, identifying the onset of thermoacoustic instability remains elusive due to spatial variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…First, we analyze the results obtained for experiments with a combustor length of 1100 mm, operating at ṁfuel of 34 SLPM with the bluff-body positioned 45 mm from the dump plane and where ṁair changes at a rate of 3 SLPM/s. We name this set of operating conditions and experimental configurations used in [15] as the reference experimental configuration (REC) for the purpose of comparing the results. For all the subsequent figures, instead of discussing the plots with respect to ṁair , we describe the figures using the global equivalence ratio φ.…”
Section: A Characterization Of the Phase Transition At Different Oper...mentioning
confidence: 99%
See 2 more Smart Citations
“…First, we analyze the results obtained for experiments with a combustor length of 1100 mm, operating at ṁfuel of 34 SLPM with the bluff-body positioned 45 mm from the dump plane and where ṁair changes at a rate of 3 SLPM/s. We name this set of operating conditions and experimental configurations used in [15] as the reference experimental configuration (REC) for the purpose of comparing the results. For all the subsequent figures, instead of discussing the plots with respect to ṁair , we describe the figures using the global equivalence ratio φ.…”
Section: A Characterization Of the Phase Transition At Different Oper...mentioning
confidence: 99%
“…Recently, in a bluff-body stabilized dump turbulent combustor, Raghunathan et al [15] showed early local growth of flame fluctuations prior to the onset of thermoacoustic instability. In particular, they revealed significant growth of local heat release rate fluctuations occurring at certain zones within the combustor, located around the bluff-body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation